Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
3x = 14
Step-by-step explanation:
Add the two equations.
5x + (-2x) = 3x
(-y) + y = 0
6 + 8 = 14
3x = 14.
Step-by-step explanation:
5x - y = 6 and -2x + y = 8
1/ 5x - y = 6
=> y = 5x - 6
2/ -2x + y = 8
Substitute 1/ into 2/ we will have:
-2x + (5x - 6) = 8
=> -2x + 5x - 6 = 8
=> 3x = 14
=> x = [tex]\frac{14}{3}[/tex] <=> y = [tex]\frac{52}{3}[/tex]
- However, the question asked for the final equation when adding 5x - y = 6 and -2x + y = 8 => The correct answer will be: 3x = 14
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.